Molecular Docking, Synthesis, Characterization of Sulphamethoxazole Schiff Base Metal Complexes and its Antibacterial, Anti-Inflammatory and Anti Depressant Activity - Mugdivari Sangeetha; R. Gandhimathi; Shushma Voggu; Jammula Prathyusha (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
The goal of the study is to create metal complexes that are higher than schiff’s base using metals like copper, metal, and metallic element, as well as to synthesis schiff’s base, an antibacterial medication, using aromatic organic compounds like p-diethyl amino benzyldehyde and p-dimethyl amino benzyldehyde. Schiff bases are versatile organic compounds which are widely used and synthesized by condensation reaction of different amino compound with aldehydes or ketones known as imine. Schiff base ligands are considered as privileged ligands as they are simply synthesized by condensation. The synthesized schiff’s bases were regenerate to its ion Schiff bases by treating with methyl group halide. The ion Schiff bases were regenerate to metal complexes by treating with metals like CuCl2, ZnCl2 and CdCl2. All the synthesized compounds were characterised by Elemental analysis, IR and 1H proton magnetic resonance. Docking study was performed to know the interaction of binding sites with protein receptor using MAO-B enzymes (PDB ID: 2BK5) and COX-2 enzyme (PDB ID: 5IKR) by Virtual Screening software for Computational Drug Discovery. Synthesized metal complexes were evaluated for antibacterial, anti inflammatory and antidepressant activity. Copper metal complexes showed potent antibacterial and anti-inflammatory activity. Significant anti-depressant activity was shown for 2A2 and 2B2 zinc metal complexes.